Studi Empiris mengenai Dampak Return on Assets (ROA) terhadap Harga Saham Perusahaan Sub-sektor Penerbangan yang Terdaftar di BEI Periode 2020–2023. - Fitriani Fitriani; Dava Wardhana; Agoes Hari Edy Wibowo (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the effect of Return On Assets (ROA) on stock prices in airline subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research method used is quantitative with a causal associative approach. The research sample includes PT Garuda Indonesia Tbk, PT AirAsia Indonesia Tbk, and PT Jaya Trishindo Tbk. The data used are secondary data in the form of annual financial reports obtained from the official IDX website. Data analysis was conducted using simple linear regression, t-test, and the coefficient of determination with SPSS version 25. The results indicate that Return On Assets (ROA) has a positive and significant effect on stock prices, with a t-value of 2.520 greater than the t-table value of 2.228 and a significance level of 0.030 < 0.05. The coefficient of determination (R²) of 0.388 shows that ROA explains 38.8% of stock price variations, while the remaining 61.2% is influenced by other factors outside the research model